Women's NGOs as intermediaries in development cooperation: findings from research in Tanzania. Issue 7 (3rd October 2017) - Grantham, Kate; Baruah, Bipasha
ABSTRACT: This article employs research conducted with the Kivulini Women's Rights Organization in Tanzania to discuss opportunities, constraints, and broader lessons about the role of women's NGOs as intermediaries in development projects. Findings reveal that women's NGOs often have insecure positions in development projects and are undervalued by executing agencies because advocating for gender equality is perceived as a "natural" extension of women's roles in patriarchal societies. Women's NGOs are "feminised" and consequently trivialised in their role as intermediaries, putting gender equality objectives at risk of attrition or abandonment. Under certain circumstances, women's NGOs can be pushed out of partnership projects altogether.